Employment-at-Will, Employee Rights, and Future Directions for Employment - Radin, Tara J. (Business ethics quarterly, 2003)
During recent years, the principle and practice of employment-at-will have been under attack. While progress has been made in eroding the practice, the principle still governs the philosophical assumptions underlying employment practices in the United States, and, indeed, EAW has been promulgated as one of the ways to address economic ills in other countries. This paper will briefly review the major critiques of EAW. Given the failure of these arguments to erode the underpinnings of EAW, we shall suggest new avenues for approaching employment issues to achieve the desirable goal of employee dignity and respect.